2015
DOI: 10.1073/pnas.1415037112
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for substrate specificity of an amino acid ABC transporter

Abstract: ATP-binding cassette (ABC) transporters are ubiquitous integral membrane proteins that translocate a variety of substrates, ranging from ions to macromolecules, either out of or into the cytosol (hence defined as importers or exporters, respectively). It has been demonstrated that ABC exporters and importers function through a common mechanism involving conformational switches between inwardfacing and outward-facing states; however, the mechanism underlying their functions, particularly substrate recognition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 45 publications
3
55
0
2
Order By: Relevance
“…Our findings suggest that PC and PE lipids access the internal drugbinding pocket through the portals P1 and P2, which has also been reported for drug molecules in several studies [1] [4]. It has been also suggested that a positively charged ring of residues such as Arg and Lys [63] [64], could drive substrates towards the cavity, and promote lipid-protein interactions in ABC transporters in general via electrostatic interactions. From our simulations, two binding hot spots at P1 were identified: Lys230 (H4), and Arg355 (H6).…”
Section: Key Binding Residues For Lipid-uptake In P-gpsupporting
confidence: 83%
“…Our findings suggest that PC and PE lipids access the internal drugbinding pocket through the portals P1 and P2, which has also been reported for drug molecules in several studies [1] [4]. It has been also suggested that a positively charged ring of residues such as Arg and Lys [63] [64], could drive substrates towards the cavity, and promote lipid-protein interactions in ABC transporters in general via electrostatic interactions. From our simulations, two binding hot spots at P1 were identified: Lys230 (H4), and Arg355 (H6).…”
Section: Key Binding Residues For Lipid-uptake In P-gpsupporting
confidence: 83%
“…Deletion of the alanine racemase gene, alrA (dal), has previously been shown to result in auxotrophy for D-alanine (9). We sought to use this property to determine if a specific D-alanine uptake system was present or if uptake was mediated by transporters with degenerate specificity as has been suggested for some other amino acid uptake systems (27). So we characterised the growth of a strain lacking the conditionally essential alanine racemase, alrA (strain RD180) in a LB growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic, biochemical and structural analysis revealed the presence of low-affinity ligand-binding sites in the TMDs of the E. coli maltose/maltodextrin system (Shuman, 1982;Covitz et al, 1994;Khare et al, 2009;Bordignon et al, 2010;Cui et al, 2010;Chen, 2013) and of the arginine/histidine ABC transporter from the thermophile T. tengcongensis (Yu et al, 2015), both of which belong to the type-I subfamily of ABC import systems (Locher, 2016;Lewinson and Livnat-Levanon, 2017). Mutational analysis of the internal binding sites in the MalF and MalG TMDs revealed that it is essential for the functioning of the maltose/maltodextrin ABC transporter (Covitz et al, 1994;Ehrle et al, 1996;Steinke et al, 2001;Khare et al, 2009).…”
Section: Discussionmentioning
confidence: 99%